2001
DOI: 10.2134/jeq2001.3051675x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Biomacromolecules during High‐Rate Composting of Wheat Straw–Amended Feces

Abstract: Pig (Sus scrofa) feces, separately collected and amended with wheat straw, was composted in a tunnel reactor connected with a cooler. The composting process was monitored for 4 wk and the degradation of organic matter was studied by two chemical extraction methods, 13C cross polarization magic angle spinning (CPMAS) nuclear magnetic resonance (NMR) and pyrolysis gas chromatography-mass spectrometry (GC-MS). Wet-chemical extraction methods were not adequate to study the degradation of specific organic compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 33 publications
3
28
0
3
Order By: Relevance
“…Carbon content is lost during composting in the form of CO 2 as metabolic end-product while total nitrogen content increase due to anabolism of cell structure, enzymes, hormones, etc. The increase of total nitrogen content during composting was in the agreement with other studies (Veeken et al 2001;Lee et al 2002) where they showed that straw with sludge amendment increased inorganic nitrogen content to soil. As a consequence, the C/N ratio decreased during the composting period.…”
Section: Resultssupporting
confidence: 92%
“…Carbon content is lost during composting in the form of CO 2 as metabolic end-product while total nitrogen content increase due to anabolism of cell structure, enzymes, hormones, etc. The increase of total nitrogen content during composting was in the agreement with other studies (Veeken et al 2001;Lee et al 2002) where they showed that straw with sludge amendment increased inorganic nitrogen content to soil. As a consequence, the C/N ratio decreased during the composting period.…”
Section: Resultssupporting
confidence: 92%
“…Signals around 72-74 ppm were due to C2, C3 and C5 of cellulose as well as carbons from xylans [52]. The peak at 65 ppm may be assigned to crystalline components of C6 in hexose or C5 in pentose [53,54]. Carbohydrate structures have been reported to remain almost intact in humic and fulvic acids [50].…”
Section: Fluorescence Spectramentioning
confidence: 99%
“…Furthermore, Py-FIMS was used for characterizing four phases of cow manure composting (van Bochove et al 1996). Veeken et al (2001) investigated the evolution of macromolecules in a composting process of wheat straw and pig manure using pyrolysis gas chromatography-mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%